ANALYSIS OF FACTORS SHAPING CUSTOMER LOYALTY AT UD. SDS IN THE CITY OF MALANG - Santosa, Angela Grace; Herdinata, Christian (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
UD. SDS is a business that offers a wide range of building material products needed for construction, renovation, and daily needs. The company was founded in 2009 and is located at Jalan Galunggung No 76, Klojen, Malang City. UD. SDS offers various product variants ranging from wall paint, wood paint, cement, iron, concrete, to plywood. The purpose of this study is to determine the factors that shape customer loyalty at UD. SDS. In this study, there are 22 variables used as factors that are assumed to form customer loyalty, so that the results can be used by UD. SDS to develop a strategic framework to shape the success of UD. SDS in Malang City. This study has a sample size of 286 respondents who are UD SDS’s customers. The method in this research is quantitative, with the Exploratory Factor Analysis (EFA) analysis method using Statistical Product and Service Solution (SPSS). This research shows that the main shaping factors for UD SDS’s customer loyalty is personalized customer service and its elements and the supporting shaping factor is social and environmental responsiveness and its elements. Customers feel that if customer service personalization is provided well, then customers tend to be more interested and encourage customer loyalty. Customers feel that if a store has good social and environmental responsiveness, then customers tend to feel comfort and convenience and have more intention to make purchasing decisions and have loyalty in the future.